Frequency and Implications of Paratracheal Lymph Node Metastases in Resectable Esophageal or Gastroesophageal Junction Adenocarcinoma. Issue 4 (April 2021) - Harada, Kazuto; Hwang, Hyunsoo; Wang, Xuemei; Abdelhakeem, Ahmed; Iwatsuki, Masaaki; Blum Murphy, Mariela A.; Maru, Dipen M.; Weston, Brian; Lee, Jeffrey H.; Rogers, Jane E.; Thomas, Irene; Shanbhag, Namita; et al.
Abstract : Objective: We aimed to evaluate the frequency of paratracheal lymph nodes (LN) metastases and their prognostic influence. Summary Background Data: Paratracheal LNs are considered regional nodes in the esophageal cancer classification, but their metastatic rate and influence on survival remain unclear. Methods: One thousand one hundred ninety-nine patients with resectable esophageal or gastroesophageal junction adenocarcinoma (EAC) (January 2002 and December 2016) in our Gastrointestinal Medical Oncology Database were analyzed. Paratracheal LNs were defined as1R, 1L, 2R, 2L, 4R, and 4L, according to the 8th American Joint Committee on Cancer classification. Results: Of 1199 patients, 73 (6.1%) had positive paratracheal LNs at diagnosis. The median overall survival (OS) of 73 patients with initial paratracheal LN involvement was 2.10 years (range 0.01–10.1, 5-yrs OS 24.2%). Of 1071 patients who were eligible for recurrence evaluation, 70 patients (6.5%) developed paratracheal LN metastases as the first recurrence. The median time to recurrence was 1.28 years (range 0.28–5.96 yrs) and the median OS following recurrence was only 0.95 year (range 0.03–7.88). OS in 35 patients who had only paratracheal LN recurrence was significantly longer than in patients who had other recurrences (median OS 2.26 vs 0.51 yrs, 5-yrs OS; 26.8% vs 0%, P < 0.0001). Higher T stage (T3/T4) was an independently risk factor for paratracheal LN recurrence (odds ratio 5.10, 95% confidence interval 1.46–17.89). We segregated patients in 3 groups based on the distance of tumor's proximal edge to esophagogastric junction (low; ⩽2 cm, medium; 2.0–7.0 cm, and high; >7.0 cm). Paratracheal LN metastases were more frequent with the proximal tumors (low, 4.2%; medium, 12.0%; high, 30.3%; Cochran–Armitage Trend test, P < 0.001). Conclusion: Paratracheal LN metastases were associated with a shorter survival in resectable EAC patients. Alternate approaches to prolong survival of this group of patients are warranted. Abstract : Supplemental Digital Content is available in the text